Determinants of diabetes in prolanis patients - Donal Nababan; Rulihta Sembiring; Daniel Ginting (Universitas Aisyah Pringsewu, 2023)
Diabetes is a major health problem because nearly half a billion people live with diabetes worldwide. The purpose of this study was to analyze the determinants of diabetes in prolanis patients in the working area of Tigapanah Public Health Center, Karo district. This research is an analytical research. The population of this study were 72 people and the number of samples was 42 people. Data was collected using a questionnaire and then analyzed by univariate, bivariate, and multivariate. The chi-square test showed family history (p-value = 0.021), diet (p-value = 0.009), physical activity (p-value = 0.006), and knowledge (p-value = 0.015). The dominant independent variable was diet (p-value = 0.010 (p less than 0.025); POR = 1.618; CI = 1.49 – 1.79). The conclusion of the study is that there is a relationship between family history, diet, physical activity, knowledge and diabetes mellitus. Suggestions for respondents to be able to adopt a healthy and balanced diet. Abstrak: Diabetes merupakan masalah kesehatan utama karena hampir setengah miliar orang hidup dengan diabetes di seluruh dunia. Tujuan penelitian ini adalah untuk menganalisis determinan diabetes pada pasien prolanis di wilayah kerja puskesmas Tigapanah kabupaten Karo. Penelitian ini adalah penelitian analitik. Populasi penelitian ini sebanyak 72 orang dan jumlah sampel sebanyak 42 orang. Pengumpulan data dilakukan dengan menggunakan kuesioner kemudian dianailisis secara univariat, bivariat, dan multivariat. Uji chi-square menunjukkan riwayat keluarga (p-value = 0.021), pola makan (p-value = 0.009), aktivitas fisik (p-value = 0.006), pengetahuan (p-value = 0.015). Variabel independen yang dominan adalah pola makan (p- value = 0.010 (p kurang dari 0.025); POR = 1.618; CI = 1.49 – 1.79). Kesimpulan dari penelitian adalah ada hubungan riwayat keluarga, pola makan, aktivitas fisik, pengetahuan dengan penyakit diabetes mellitus. Saran agar responden mampu menerapkan pola makan sehat dan seimbang.